A hemithioindigo molecular motor for metal surface attachment. Issue 7 (31st October 2018) - Hoffmann, Kerstin; Mayer, Peter; Dube, Henry
Abstract : We report on the synthesis of a hemithioindigo molecular motor bearing thioether feet for metal surface attachment and a comprehensive study of its light induced unidirectional motion in solution. Abstract : Functionalization of surfaces with responsive molecular entities is currently an important research field allowing the organization of molecular functions in space in a defined way and thus accessing emergent properties not observed in solution. Herein we report on the synthesis of a hemithioindigo molecular motor bearing thioether feet for surface attachment on its thioindigo fragment. We also give a full theoretical description of its ground state energy profile together with an experimental evaluation of the visible light driven unidirectional rotation in solution. Comparison with the corresponding unsubstituted original motor shows that after feet-attachment the hemithioindigo molecular motor is fully operative with a similar maximum attainable speed and degree of unidirectionality.